Influence Of Project Plans On The Outcome Of Construction Projects Procured By Design-build (Db) In Nigeria - Idoro, Godwin Iroroakpo (Penerbit Universiti Sains Malaysia, 2012)
This study evaluates the influence of project plans on the outcome of design-build projects. The purpose is to ascertain whether the level of use of project plans can be utilised to improve the outcome of projects procured by the design-build method. To achieve this purpose, a field survey of 42 projects procured by the design-build method and selected by stratified random sampling was conducted. Data were collected with the aid of structured questionnaires and analysed using percentage, mean and the Spearman correlation test. The results of the study indicate that the level of use of project plans has significant influence on some parameters of the design-build projects' outcome. The results also indicate that the inception, design, tendering and construction plans are not prepared in many of the projects sampled. The study concludes that the level of use of project plans can be used to reduce the high time and cost overruns recorded in design-build projects and that there is room for stakeholders to increase the level of use of project plans in design-build projects. The study suggests that stakeholders should ensure that the required project plans are prepared when projects are procured by design-build.